2017
DOI: 10.2196/preprints.9044
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-Harm, Suicidal Behaviours, and Cyberbullying in Children and Young People: Systematic Review (Preprint)

Abstract: Evidence before this studyThe adverse impact of bullying on children and young people has long been recognised. The rise of electronic communication has led to "cyberbullying". Two previous systematic reviews exploring the association between cyberbullying involvement and self-harm (SH)/suicidal behaviours included only three quantitative studies on this topic but the field has rapidly expanded. Added value of this studyWe conducted a comprehensive search of all available literature form 1 st January 1996 to 3… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…Other findings include; that loss of self-esteem and failure to achieve are sources through which social media could cause depression, that cyber bulling may also lead to depression. This supports the finding by John et al (2018) who after a research concluded that victims of cyber bullying are at greater risk of depression, self-harm, and suicide behaviours than non-victims.…”
Section: Discussionsupporting
confidence: 87%
“…Other findings include; that loss of self-esteem and failure to achieve are sources through which social media could cause depression, that cyber bulling may also lead to depression. This supports the finding by John et al (2018) who after a research concluded that victims of cyber bullying are at greater risk of depression, self-harm, and suicide behaviours than non-victims.…”
Section: Discussionsupporting
confidence: 87%
“…Extant research supports this theory, with results showing that offline racial discrimination is linked to increased suicidal ideation among Black youth. 5,6 In addition, cyberbullying is associated with increased suicidal ideation, 7 and Black adolescents have an average of 5 racially discriminatory experiences daily, mostly occurring online. 8 Research is needed to determine whether online racial discrimination (ORD), defined as demeaning or excluding an individual or group on the basis of race through the use of symbols, video, images, text, and voice, may contribute to increased suicidal ideation among Black youth.…”
mentioning
confidence: 99%